Edukasi Bahaya Logam Berat dalam Tubuh dan Sumber Kontaminannya - Djamilah Arifiyana; Vika Ayu Devianti; Ratih Kusuma Wardani (Jurnal Abdi Masyarakat Kita, 2023)
Contamination in aquatic systems has an indirect impact on survival. One type of contamination of the aquatic system is the presence of heavy metal contamination. Continuous exposure to heavy metals can cause kidney, liver, neurological disease, vascular disease, and cancer. Sources of heavy metals come from the mining industry, paint industry, use of pesticides, etc. To provide insight to the public, it is necessary to conduct education about the sources of heavy metal contamination and its impact on the body. The implementation of this community service activity is in the form of webinars for active students. A total of 63 students participated in this educational activity. The selection of students as the target community is based on their role in society. The methods used in this activity include presentations by lecturers and students, as well as discussions and questions and answers. To measure knowledge, pre-test and post-test were conducted.